Constraints on the nature of the basement of the Junggar terrane indicated by the Laba Ordovician continental arc. Issue 1 (2nd January 2020) - Wu, Chu; Hong, Tao; Xu, Xing-Wang; Li, Hao; Ke, Qiang; Li, Hang; Dong, Lian-Hui
ABSTRACT: With the improvement of regional geological research surrounding the Junggar Basin, whether Junggar terrane has a Precambrian basement is becoming one of the most popular topics of study. The Alashankou area, situated in the west of the Laba unit, is a westernmost trailing-shaped part of the Junggar terrane in the Central Asian Orogenic Belt. Precise petrological, geochronological and geochemical constraints of the metamorphic igneous rocks in the Alashankou area provide a better understanding of the tectonic evolution of the Laba unit, and combining these constraints with the previously geochronological and geophysical results is crucial to reevaluate the nature of the basement of the Junggar terrane. In this paper, our diagnostic results reveal that (1) the two-mica plagioclase schist, biotite amphibole plagioclase schist and granitic mylonite were formed in 447.6 Ma, 443.7 Ma and 428.8 Ma, and their protoliths are possible acidic tuff, andesite, and granite (porphyry), respectively; (2) these rocks have geochemical signatures that originated from typical continental arcs, including intermediate-acid calc-alkaline series rocks; the enrichment of enriched in large ion lithophile elements (LILE), Zr, and Hf; the depletion of Ta, Nb, P and Ti; (3) the granitic mylonite has 0.90 Ga–2.58 Ga inherited zircons, low εHf(t) to 8.11 and old TDM2 (Hf) age to 2.91 Ga, suggesting the existence of a Precambrian crust or similar materials as their sources. Based on these parameters, we suggest that (1) the metamorphic igneous rocks were formed in an Early Paleozoic continental arc along the west margin of the Junggar terrane, and (2) the Southern and Eastern Junggar Basin possibly has Precambrian basements, whereas the Northern Junggar Basin consists of accretionary complexes. Southward subduction of the Junggar oceanic plate beneath the Laba unit occurred in the Late Ordovician to Middle Silurian, and the regional continental accretion and metamorphism of the Laba unit happened in the Early Devonian. Graphical abstract: